A simple high-performance liquid chromatography assay for on-line determination of catecholamines in adrenal gland by direct injection on an ISRP column - Sanchez, A. [UNESP]; Toledo-Pinto, E. A.; Menezes, M. L.; Pereira, O. C. M. (Elsevier, 2004)
In the present research, assays were improved for the determination of catecholamines in adrenal gland. High-performance liquid chromatography with electrochemical detection was employed for quantitative analysis. The method involved direct injection of acid extract on to a serum albumin dimethylocadecyl-silane (HSA-C18) and the utilization of phosphate buffer (pH = 3.0): methanol (97:3 v/v), 0.025 g heptanosulfonic acid and 0.0025 g EDTA as mobile phase. The detection was obtained using an electrochemical detector L-ECD-6A-Shimadzu with a potential of the 85 mV. Identification was based on retention time. Quantification was performed by automatic peak-area determination. The detection limit is equal to 0.5 ng ml(-1). The HPLC method with electrochemical detection proposed here permits good separation of catecholamines in samples of adrenal gland from rats. The method has various advantages: fast, high precision and good selectivity and do not require sample treatment. The immobilization stress during 5 min did not provoke alteration in catecholamines contains in rat adrenal gland, due to the short time of the stress exposure. This study shows that the catecholamines (norepinephrine and epinephrine) adrenal increased significantly after the acute immobilization stress during 30 min as compared to control group. This increase probably is due to the emotional component of the immobilization stress. In conclusion, our studies suggest an effective participation of the adrenal glands to maintain the homeostasis of organism to the stressful conditions.
Keywords: Catecholamines; Immobilization stress; Adrenal gland; Column liquid chromatography; On-line analysis; Rat